UNESCO’S STRATEGY FOR REBUILDING HIGHER EDUCATION IN CRISIS AND EMERGENCY SITUATIONS - Gladushyna, Olesya (The Modern Higher Education Review, 2017)
The paper analyzes the UNESCO’s policy on protecting and development of the contemporary higher education (HE) which faces many challenges on the way towards its development, sustainability, and improvement. Moreover, the articles posits that the importance of determining crisis and emergency factors which impact the HE system in order to comprehend the role of UNESCO and its actions in supporting the HE system and universities in different regions of the world. Therefore, the concepts and characteristics of crisis and emergency risks are provided, the UNESCO’s strategies in responding to the challenges of the contemporary HE in terms of its instability and potential external threats are defined as well as the relevance and effectiveness of mode of operations applied by UNESCO in regulating conflicts and other onerous situations pertinent to HE sector is reasoned.